1989
DOI: 10.1111/j.1476-5381.1989.tb12671.x
|View full text |Cite
|
Sign up to set email alerts
|

The spontaneous electrical and mechanical activity of human bronchial smooth muscle: its modulation by drugs

Abstract: 1 Tissue taken at operation was used to study the electrical and mechanical properties of human bronchial smooth muscle with intracellular microelectrodes and isometric recording of tension changes. 2 Over 90% of the muscle strips exhibited spontaneous tone and 70% produced spontaneous phasic contractions. The resting membrane potential of the smooth muscle cells ranged between -40 to -50 mV with a mean value of -44.9 + 5.2 mV (n = 92 ± s.d.). Spontaneous oscillations of the membrane potential (slow waves) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…In the adult human and animal tissue the airway muscle phasic activity is intermittent and not always present (2)(3)(4). In the present study we observed the highest spontaneous and U46619-induced bronchial muscle activity in the fetal rat at term with an average frequency of 10 contractions/min.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In the adult human and animal tissue the airway muscle phasic activity is intermittent and not always present (2)(3)(4). In the present study we observed the highest spontaneous and U46619-induced bronchial muscle activity in the fetal rat at term with an average frequency of 10 contractions/min.…”
Section: Discussionsupporting
confidence: 52%
“…As opposed to the tonic muscle activity that determines the airway caliber and is responsible for bronchoconstriction, phasic spontaneous activity has been described in the trachea and smaller airway muscle of adult rabbits (2), humans (3,4) and guinea pigs (5). This phasic activity, however, is intermittent and not present in all airway smooth muscle in vitro preparations.…”
mentioning
confidence: 99%
“…One end of the strip was tied to an isometric transducer (TB-612T; Nihon Kohden, Tokyo, Japan) and the other end to a hook at the bottom of the bath. The strips were set up with an initial tension of 0.1–0.2 g, with which the maximal change in tension was obtained in previous studies [20, 21, 22], and then equilibrated for 1–3 h with Krebs solution. The change in isometric tension was recorded using a pen recorder.…”
Section: Methodsmentioning
confidence: 99%
“…In guinea pig airways, this tone appears to be dependent on prostanoids and not on intrinsic innervation (Orehek et al, 1975). In human airways, however, the role of prostanoids is unclear since both enhancement (Ito et al, 1985) and reduction (Ito et al, 1989) of intrinsic tone have been described after inhibition of cyclooxygenase.…”
Section: Intrinsic Tonementioning
confidence: 99%
“…In addition, peptidoleukotrienes may be involved because inhibition of 5-lipoxygenase decreased intrinsic tone (Ito et al, 1989). Mansour and Daniel (1986) expressed the responses of guinea pig tracheas on a scale between maximal relaxation and maximal tension in response to carbachol.…”
Section: Intrinsic Tonementioning
confidence: 99%